Emergency notification - Chandler, Robert C. (PSI business security, 2010)
To grasp the importance of emergency notification, imagine this scenario: A shooter is on the loose at a college campus. Chaos reigns. To contain the situation, campus personnel need to communicate immediately and efficiently, not only with the students, faculty, and staff, but also the local police, federal law enforcement, and media. Effective emergency notification makes things 'right, ' it allows the right message to reach the right people at the right time, facilitating the right response. Emergency Notification explains how. This book offers must-know information for business security, senior management, human resources staff, government policymakers, and emergency planners, examining what, when, how, why, and with whom to communicate during crises. This text also covers risk communication, message mapping, information loading, audience comprehension, and practical issues like testing emergency notification systems